LncRNA Xist Contributes to Endogenous Neurological Repair After Chronic Compressive Spinal Cord Injury by Promoting Angiogenesis Through the miR-32-5p/Notch-1 Axis - Cheng, Xing; Xu, Jin; Yu, Zhengran; Xu, Jinghui; Long, Houqing (Frontiers in Cell and Developmental Biology, 2020)
Endogenous repair after chronic compressive spinal cord injury (CCSCI) is of great clinical interest. Ischemia−hypoxia-induced angiogenesis has been proposed to play an important role during this repair process. Emerging evidence indicates that long non-coding RNAs (lncRNAs) are involved in the pathophysiological processes of various diseases. Here, we identified a lncRNA (Xist; X-inactive specific transcript) with upregulated expression in cervical spine lesions during endogenous neurological repair in CCSCI rats. Therapeutically, the introduction of Xist to rats increased neurological function in vivo as assayed using the Basso, Beattie, and Bresnahan (BBB) score and inclined plane test (IPT). We found that the introduction of Xist enhanced endogenous neurological repair by promoting angiogenesis and microvessel density after CCSCI, while depletion of Xist inhibited angiogenesis and cell sprouting and migration. Mechanistically, Xist promoted angiogenesis by sponging miR-32-5p and modulating Notch-1 expression both in vitro and in vivo. These findings suggest a role of the Xist/miR-32-5p/Notch-1 axis in endogenous repair and provide a potential molecular target for the treatment of ischemia-related central nervous system (CNS) diseases.